(untitled) (Revista Contexto & Educação, 2024)
The research whose partial results are presented in this article is linked to the CAPES Research Project/Postgraduate Development Program (PDPG) Alterity in Postgraduate Studies: “People with disabilities in stricto sensu postgraduate education in Brazil: ethics of otherness in the construction of public inclusion policies”, developed within the scope of the Postgraduate Program in Human Rights at the Universidade Regional do Noroeste do Estado do Rio Grande do Sul (Unijuí). The topic gains prominence in the academic field as there are still many obstacles to the implementation of the inalienable rights of people with disabilities, despite some advances regarding the right to education. The problem can be summarized as follows: what are the difficulties in accessing and remaining for people with disabilities on the gym benches and the need for a perspective based on inclusion based on public policies. As a hypothesis initially launched to the research problem, one can assert the difficulty of social insertion in the area of education for this group of people, due to the period of invisibility and exclusion. The theoretical, conceptual and methodological contribution that supports the study undertaken presents a reflection on how the lack of adequate implementation of public policies results in borders and limits for this group of students to access higher education, based on the analysis of statistical data on this group’s education. population contingent, from a critical assessment of legislation and public policies from special education to inclusive education and the challenges to transform higher education into a space for effective inclusion of this group of people and the role of how public policies are necessary in reducing the gap between the programming (legislation) and operational (public policies) dimension of implementing the right to education, through specialized educational service policies, assistive technologies and accessibility. The study presented here is developed based on the hypothetical-deductive method and the selection of bibliography that forms the theoretical framework based on a survey of scientific productions and existing legislation/regulation on the subject.